PLS Equation Model of Student Loyalty based on Gender in IR 4.0 Environment - Bahtiar Jamili Zaini; Rosnalini Mansor; Norhayati Yusof; Mohammad Nizam Sarkawi (International Journal of Supply Chain Management, 2019)
Students loyalty and attrition is an important issue for university authorities.Â  Earlier studies have discovered that many factors influencing student loyalty towards their higher learning institutions such as student satisfaction, university image, student trust, and service quality. However, these factors have high relationship correlated with each other. Therefore, this study used the Partial Least Square (PLS) to create a path model which shows the relationship between all factors related to student loyalty. The results from this study revealed that student satisfaction is the most important factors that influence student loyalty, followed by image of university and student commitment. Analysis based on gender shows that female student model have a same pattern with overall student loyalty model but the male student loyalty model is simpler just consist student satisfaction. On the other hand, factors technology, social environment and quality of instructor gave a great influence towards student satisfaction. Therefore, in order to improve student loyalty, university should keep on improving to satisfy studentsâ€™ requirement.